The Social Construction of Family Roles in Migrant Worker Income Management to Build Family Economy - Tutik Sulistyowati; Wahyudi Wahyudi; Salahudin Salahudin; Iradhad Taqwa sihidi (Universitas Muhammadiyah Yogyakarta, 2022)
This paper aims to explain the social construction of family roles in migrant workers’ income management to build the family economy viewed from the aspects of knowledge and skills in management, as well as attitudes and actions in managing the income. This research was conducted using a descriptive method with a qualitative approach. The subjects were selected based on proportional sampling, namely people who live close to the families of migrant workers, extended families of migrant workers, and community leaders. The results of this study indicate that, in reality, some couples of migrant worker families can manage their income and household well, resulting in the income of migrant workers that does not have meaningful impact on the family. The findings of this study contribute to developing a theory of social construction, where reality is the result of individual understanding, which is used as a shared understanding in the community. This shared understanding gives a new stigma to the reality of migrant worker families. The limitation of the research is that the data used are only obtained from subject interview data and case observations in the field, so the research findings limitedly describe the study of social construction in general. Future research needs to use data obtained not only from field observations and subject interviews, but also from the data from Scopus database and the Web of Science (WoS) database.